Pensions in Crisis : Europe and Central Asia Regional Policy Note - World Bank (Washington, DC, 2014)
The financial crisis has significantly impacted pension systems in the Europe and Central Asia region (ECA) tempting governments to make policy changes in response to the increased pension deficits they are facing. The crisis exacerbates the existing financial imbalance in the public pension systems by reducing contribution revenues sharply while leaving expenditures constant or even higher. The crisis also resulted in a sharp drop in financial asset values which affects pensions provided by funded pillars. Consequently, no pension system, however structured, has been immune to the crisis. Despite the severity of the financial crisis, it pales in comparison to the demographic crisis which the region will face. Therefore, countries are urged not to make long-term policy changes to address short-run fiscal concerns. Any short-run responses should be consistent with strategies to address the long-run challenges to the pension system. The long-run focus should include: (i) protecting the purchasing power of pensioners and fiscal sustainability of the system, both during the crisis and beyond, by shifting to inflation indexation of pensions, (ii) encouraging individuals to work more and longer by raising retirement ages, equalizing retirement ages between men and women, and curbing early retirement, and (iii) enhancing public awareness of the increasingly limited capacity of publicly provided pensions as populations age.